PKM MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI PENGEMBANGAN BISNIS THRIFTING SHOP SEPATU ONLINE - Dwi Oktarini, Rahmi; Choiriya, Nabila; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Shoes play a significant role in today's fashion and style. Consequently, consumers consider various factors such as product quality, price, and promotions when making purchasing decisions. In this regard, we, as students of Indo Global University, conducted independent research and socialization activities at the online shoe retailer "Laroza Second Brand." Utilizing social media platforms such as Facebook, Instagram, and TikTok, online businesses effectively promote and sell shoes. Social media, as an online tool with human users, facilitates live broadcasts for promoting and selling products. With this in mind, we visited the location to observe and assist in understanding how social media technology is utilized to generate revenue. This community service initiative involved collaboration between lecturers and students from Indo Global Mandiri University to support MBKM (Community Service Learning).